Analisis Risiko Pekerjaan Fire Fighting System pada Proyek Sktt 150 Kv di Jembatan Suramadu dengan Metode Hazard Identification Ris Assessmentand Risk Control (HIRARC) - Arif Sasmito (Syntax Corporation Indonesia, 2023)
Workplace accidents are all unplanned events that result in or have the potential to cause injuries, illnesses, damage, or other losses (AS/NZS 4801, 2001 Standard). The objectives of this study are to identify potential hazards associated with the Fire Fighting System Work of the 150 KV SKTT Project at the Suramadu Bridge and to apply the HIRARC method to identify risks associated with this work. This research is descriptive in nature and utilizes a mixed methods analysis, combining both quantitative and qualitative approaches. The study is conducted on the construction work of the 150 KV High Voltage Cable Channel (SKTT) from GI Kenjeran to Tower 35 Bangkalan, passing through the Suramadu Bridge in Surabaya, East Java. The object of this research is the Fire Fighting System Work of the 150 KV SKTT Project at the Suramadu Bridge. An illustration of the research object has been taken from Google. The population in this study consists of employees who are involved in the construction work of the 150 KV High Voltage Cable Channel (SKTT) from GI Kenjeran to Tower 35 Bangkalan, totaling 50 people. Based on the results of the risk assessment, it is revealed that there is 1 risk (4%) classified as Extreme Risk, 4 risks (17%) as High Risk, 6 risks (25%) as Moderate Risk, and 13 risks (54%) as Low Risk.